Literature Review: Faktor Krusial Mengoptimalkan Working Memory Anak: Literature Review: Crucial Factors in Optimizing Children's Working Memory - Sweety Valensya Lolong; Augustina Sulastri; Cicilia Tanti Utami (ITScience (Information Technology and Science), 2026)
Working memory is a short-term cognitive system that allows individuals to actively store and manipulate information in a short period of time. This capacity forms the foundation for vocabulary mastery, literacy, and mathematical reasoning during childhood development. Given its vital role in predicting academic success and socio-emotional adaptability, identifying variables capable of optimizing working memory function from an early age is urgent in educational psychology discourse. This study aims to analyze crucial factors influencing working memory optimization in children through a systematic literature review. The analysis was conducted based on a synthesis of data from various reputable journals from 2020 to 2025 and related fundamental literature. A qualitative approach was used to explore the relationship between biological factors, the environment, and technical interventions on working memory performance. The findings indicate that working memory efficiency is not static but is influenced multidimensionally. Internal factors include nutritional status, where suggestion habits have been shown to modulate verbal fluency and memory capacity. Externally, environmental stimulation through structured cognitive training, such as the n-back task, and the quality of parent-child interactions have a significant impact. However, there is a negative correlation between excessive digital media exposure (screen time) and children's auditory processing and attention abilities. Furthermore, socioeconomic disparities and emotional regulation act as moderators in the development of the neural circuitry underlying working memory. Working memory is a plastic cognitive function and is responsive to strategic interventions. Optimizing children's learning potential requires synergy between nutritional support, technology exposure management, and adaptive teaching methods. The implications of this research encourage the formulation of more holistic, evidence-based early childhood education policies.